Anti-inflammatory Activity of Glucomannan Resulting from β-mannanase Enzyme Hydrolysis in RAW 264.7 Cells - Nuraini, Nuraini; Effionora Anwar; Dian Ratih Laksmitawati; Hendig Winarno; Siti Irma Rahmawati (Faculty of Pharmacy Universitas Pancasila, 2025)
Glucomannan is a polysaccharide of the hemicellulose type, composed of glucose and mannose chains. It has the ability to form solutions that expand and thicken. The bioactivity of carbohydrates is influenced by the length of their saccharide chains. Hydrolysis can alter the structural dimensions of polysaccharides, including molecular weight, type, number, and position of substituent groups, which in turn impacts their biological activity. Various methods can modify carbohydrate structures to enhance their value, with degradation being one such method. Enzymatic degradation is particularly advantageous due to its high specificity, efficiency, and minimal side effects. Numerous studies have identified glucomannan as having immunomodulatory effects on macrophage cells. When stimulated with lipopolysaccharides, macrophages release various cytokines and inflammatory mediators, such as TNF-α, iNOS, and NO. This study explored the potential anti-inflammatory effects of glucomannan (GM) and its enzymatically hydrolyzed form (Enz-GM) on RAW 264.7 cells. The research involved degrading glucomannan using the β-mannanase enzyme, followed by in vitro testing of the degradation product (Enz-GM) for anti-inflammatory activity. This was achieved using an ELISA kit to measure the expression of IL-6, TNF-α, and iNOS. The results showed that Enz-GM at pH 9 (Mw 1.24 kDa) significantly reduced the pro-inflammatory cytokines IL-6 and iNOS (p ≤ 0.05) compared to GM, while TNF-α expression did not show a significant difference between Enz-GM and GM.